Economic reform, informal-formal sector linkages and intervention in the informal sector in developing countries: A paradox - Hassan Arvin-Rad; Arnab K. Basu; Maria Willumsen (Institute for the Study of Labor (IZA), 2010)
Within a general equilibrium framework of a developing economy with a foreign owned factor of production, this paper questions whether the informal-formal sector relationship is procyclical/ complementary - expansion or contraction in one necessarily implies an expansion or contraction in the other - when the informal sector is subject to a technological shock. We derive a necessary and sufficient condition under which a positive shock to the informal sector results in a contraction in both the size of the urban formal sector and the informal sector. Thus, although our result shows that the informal-formal sector relationship is procyclical, it nevertheless calls into question the conventional wisdom on the benefits of intervention in the informal sector of developing economies, particularly where multinational corporations sub-contract certain labor intensive stages of production to the informal sector.
Keywords: J8; R13; R23; 330; rural-urban migration; urban informal sector; technological change; Informeller Sektor; Technischer Fortschritt; Makroökonomischer Einfluss; Theorie; Entwicklungsländer